PENGARUH DISIPLIN KERJA, FASILITAS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KOPERASI SIMPAN PINJAM PRIMKOPABRI KABUPATEN KENDAL - Ulhaq, Abryan Zadda; Purwatiningsih, Aris Puji; Panjaitan, Roymon; Wibowo, Mochammad Eric Suryakencana (The Manager Review, 2026)
This study aims to analyze the effect of work discipline, work facilities, and work motivation on employee performance at the PRIMKOPABRI Savings and Loan Cooperative, Kendal Regency. Employee performance is an essential factor in supporting cooperative organizational effectiveness, particularly in providing optimal services to members. Preliminary findings indicated several performance-related issues, including suboptimal task completion, delays in work discipline, inadequate work facilities, and insufficient employee motivation. This research employed a quantitative approach using a survey method. The research population consisted of all 57 employees of PRIMKOPABRI Kendal Regency, and a census sampling technique was applied. Data were collected through structured questionnaires using a four-point Likert scale and analyzed using multiple linear regression with the assistance of IBM SPSS. The results show that work discipline, work facilities, and work motivation have a positive and significant effect on employee performance. Among the three variables, work facilities were identified as the most dominant factor in improving employee performance. Simultaneously, the independent variables explain 91.7% of the variance in employee performance. In conclusion, improving employee performance at PRIMKOPABRI Kendal Regency can be achieved through consistent enforcement of work discipline, adequate provision of work facilities, and continuous strengthening of employee motivation to support optimal cooperative performance.